Company's Financial Performance Before And After An Initial Public Offering: IPO At IDX In 2018 - Saraswati Telambanua; Augustina Kurniasih (Universitas Mercu Buana, 2022)
The research aims to analyze differences in a company's financial performance before and after an Initial Public Offering (IPO). The research period is one year before and one year after the IPO. The population of this research is a company that conducted an IPO and listed on the Indonesia Stock Exchange in 2018 which amounted to 55 companies. Sample withdrawal uses purposive sampling method and based on predetermined criteria samples obtained as many as 50 companies. The analysis method used is a different Wilcoxon Signed Rank Test. The results showed significant differences in liquidity performance (current ratio), solvency (debt to equity ratio), profitability (return on equity), and activity (total assets turnover) before and after the IPO. Keywords: Initial Public Offering (IPO); liquidity; solvablity; profitability; activity.